A tengeri zsákmányjog, a hatalmi szimbólumok és a tengeri csaták: Kajtár István munkássága a tengerek jogtörténetéről - Szentmiklósi, Attila (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
István Kajtás’s research on cultural history was extended to nautical questions as well. His work in this subject, especially his papers regarding the history of the Soviet-Russian fleet, the nautical symbol system, the law of sea plunder, the naval battle of Lepanto and the history of submarines will be shown in the overview honouring him.